Representations over the Earth's shape and the process of day and night from Nahua indigenous schoolchildren / Representaciones sobre la forma de la Tierra y del proceso día y noche en niños de escuelas indígenas Nahuas. Issue 2 (3rd April 2017) - Gallegos-Cázares, Leticia; Flores-Camacho, Fernando; Calderón-Canales, Elena; de la Concha, José-Manuel Posada
Abstract: This research presents the way in which children from a Nahua indigenous community build representations of the Earth's shape, as well as the process that causes day and night. Concepts from school and local culture were studied. For the first case, a questionnaire was applied to 331 children, out of which 38 children were then interviewed on the topics from the questionnaire. For the cultural ideas, three teachers from the region and 30 children from the sample were interviewed. The results show that the representations depend on the form of questioning and the existence of three models: a flat structure with a celestial dome and mechanisms that hide or remove the Sun or the Moon in order to create day and night; a spherical structure with a surrounding sky, where the Sun and Moon rise and set; and a transitional model with a hollow sphere, flat surface and celestial dome. Cultural ideas do not appear to have any influence over these models, probably due to a loss of the community's cosmogonic knowledge and the age of the children.